Solvent effects of imidazolium ionic liquids on photophysical properties of π-electron extended rhodamine dye ABPX - Kaoru Nobuoka; Shinji Enoki; Hideyuki Tanaka; Satoshi Kitaoka (Journal of Ionic Liquids)
We studied the solvent effect of imidazolium ionic liquids, which are media with microphase separation in their structure, on the cationic dye ABPX01. The proton accepting capacity of ionic liquids differs depending on their anions. Protonation of ABPX01 was enhanced in ionic liquids composed of anions with low proton accepting capacity, resulting in an increased proportion of dicationic forms. The alkyl group of the imidazolium cation caused a macroscopic change in viscosity, leading to a slight enhancement of the fluorescence intensity and an extension of the fluorescence lifetime. ABPX has potential material applications as a probe for the proton accepting capacity of ionic liquids and as a dye with AIE properties when used with suitable ionic liquids as a medium.